Effect of a calcium hydroxide/chlorhexidine paste as intracanal dressing in human primary teeth with necrotic pulp against Porphyromonas gingivalis and Enterococcus faecalis - Gondim, Juliana O. [UNESP]; Avaca-Crusca, Juliana S. [UNESP]; Valentini, Sandro Roberto [UNESP]; Zanelli, Cleslei F. [UNESP]; Spolidorio, Denise M. P. [UNESP]; Giro, Elisa M. A. [UNESP] (Wiley-Blackwell, 2012)
Background. Intracanal medication is important for endodontic treatment success as it eliminates microorganisms that persist after biomechanical preparation.Aim. To evaluate the effect of two intracanal medications against Porphyromonas gingivalis and Enterococcus faecalis in the root canals of human primary teeth with necrotic pulp with and without furcal/periapical lesion, using quantitative real- time polymerase chain reaction (qRT-PCR).Design. Thirty-two teeth with necrotic pulp were used. Twelve teeth did not present lesion, and 20 teeth presented radiographically visible furca/periapical lesion. Microbiological samples were collected after coronal access and bio- mechanical preparation. The teeth were medicated with calcium hydroxide pastes prepared with either polyethylene glycol or chlorhexidine. After 30 days, the medication was removed and a third collection was performed. Microbiological samples were processed using qRT-PCR. Data were analysed by Wilcoxon and Mann-Whitney tests (alpha = 0.05).Results. There was no significant difference in the microbiota present in the primary teeth with and without furcal/periapical lesion. Biomechanical preparation was effective in reducing the number of microorganisms (P < 0.05). The intracanal medications had similar antibacterial activity.Conclusion. The association of chlorhexidine with calcium hydroxide did not increase the antibacterial activity of the intracanal medication in the treatment of primary teeth with necrotic pulp with and without furcal/periapical lesion.